2004
DOI: 10.1177/0091270003262075
|View full text |Cite
|
Sign up to set email alerts
|

Quinidine as a Probe for the Role of P‐Glycoprotein in the Intestinal Absorption and Clinical Effects of Fentanyl

Abstract: The mechanism of individual variability in the fentanyl dose-effect relationship is unknown. The efflux pump P-glycoprotein (P-gp) regulates brain access and intestinal absorption of numerous drugs. Evidence exists that fentanyl is a P-gp substrate in vitro, and P-gp affects fentanyl analgesia in animals. However, the role of P-gp in human fentanyl disposition and clinical effects is unknown. This investigation tested the hypothesis that plasma concentrations and clinical effects of oral and intravenous fentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 34 publications
(78 reference statements)
1
48
0
3
Order By: Relevance
“…The present results showing that alfentanil is a P-gp substrate indicate that alfentanil-pupillometry studies may have the potential to detect alterations in P-gp activity. Previous pupillometry studies conducted with the P-gp substrates morphine, fentanyl, methadone, and loperamide have shown that inhibition of P-gp at the BBB by the P-gp inhibitor quinidine is modest (Kharasch et al, 2003(Kharasch et al, , 2004aSkarke et al, 2003). Because quinidine is one of the most potent compounds capable of inhibiting P-gp that is in clinical use, the likelihood of significant inhibition of P-gp at the BBB seems remote.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showing that alfentanil is a P-gp substrate indicate that alfentanil-pupillometry studies may have the potential to detect alterations in P-gp activity. Previous pupillometry studies conducted with the P-gp substrates morphine, fentanyl, methadone, and loperamide have shown that inhibition of P-gp at the BBB by the P-gp inhibitor quinidine is modest (Kharasch et al, 2003(Kharasch et al, , 2004aSkarke et al, 2003). Because quinidine is one of the most potent compounds capable of inhibiting P-gp that is in clinical use, the likelihood of significant inhibition of P-gp at the BBB seems remote.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, these compounds have the strong affinity to P-gp and inhibit P-gpmediated efflux, and may show clinically significant increase in intestinal absorption of various P-gp substrates. 41,42 P-gp substrates belonging to class II (cyclosporine) are fairly permeable, and may be well absorbed into systemic circulation. However, low dissolution rate limits the concentration of the drug at the site of absorption, thereby leading to less passive diffusion and further preventing saturation of efflux transporter.…”
Section: Intestinal Absorption Enhancement On P-glycoprotein Inhibitionmentioning
confidence: 99%
“…Some excipients are also Pgp inhibitors but these do not come within the scope of this article. CYP450 inhibitors such as quinidine can also enhance the bioavailability of CYP450-susceptible drugs on pre or coadministration [2]. However, this strategy may complicate the coadministration of other medications that are also CYP450-susceptibile; the bioavailability of concurrently administered medication might also be altered.…”
Section: Surmounting Enzymatic Barriersmentioning
confidence: 99%